Genetic Profiling Differentiates Second Primary Tumors from Metastases in Adult Metachronous Soft Tissue Sarcoma. (25th December 2008) - Fernebro, Josefin; Carneiro, Ana; Rydholm, Anders; Domanski, Henryk A.; Karlsson, Anna; Borg, Åke; Nilbert, Mef
Abstract : Purpose . Patients with soft tissue sarcomas (STS) are at increased risk of second primary malignancies, including a second STS, but distinction between metastases and a second primary STS is difficult. Patients and Methods . Array-based comparative genomic hybridization (aCGH) was applied to 30 multiple STS of the extremities and the trunk wall from 13 patients. Different histotypes were present with malignant fibrous histiocytomas/undifferentiated pleomorphic sarcomas being the predominant subtype. Results . aCGH profiling revealed genetic complexity with multiple gains and losses in all tumors. In an unsupervised hierarchical cluster analysis, similar genomic profiles and close clustering between the first and subsequent STS were identified in 5 cases, suggesting metastatic disease, whereas the tumors from the remaining 8 patients did not cluster and showed only weak pairwise correlation, suggesting development of second primary STS. Discussion . The similarities and dissimilarities identified in the first and second STS suggest that genetic profiles can be used to distinguish soft tissue metastases from second primary STS. The demonstration of genetically different soft tissue sarcomas in the same patient suggests independent tumor origin and serves as a reminder to consider development of second primary STS, which has prognostic and therapeutic implications.